Development and validation of a method for analysis of immunosuppressive drugs in human dried blood spot samples, by means of liquid chromatography coupled to tandem mass spectrometry - Larsson,Kajsa (2025)
Introduction: Dried blood spot sampling is an alternative way to conventional blood sampling that could potentially be a large benefit for certain patient groups. A good example is the transplanted patient group treated with the immunosuppressants everolimus and sirolimus. Background: The challenge is to develop a reliable quantification method based on this relatively novel sampling technique. Aims: To develop and validate a method for the quantification of everolimus and sirolimus in human dried blood spot samples. Methods: (1) Familiarization of the DBS technology and LC-MS/MS in parallel with method development. The drugs are extracted with methanol from the dried samples and analysed with LC-MS/MS. (2) Validation. Acceptance criteria are set for certain validation parameters and QC and other samples are analysed with developed method to find out if it is fit for purpose. Results: A method to extract everolimus and sirolimus using methanol from dried blood samples on filter paper and quantify the drugs using LC-MS/MS was developed. The results from the validation were promising but limited. It is possible to quantify the analytes reliably in the necessary concentration range. The method is selective, accurate and precise and obtained similar results as the routine method in liquid whole blood in a direct comparison. The analyte stability might be a challenge. Conclusion: A method for the quantification of everolimus and sirolimus in human dried blood spots was developed and partially validated. Results looks promising but further validation is needed prior to taking the method into clinical use. Keywords: Dried blood spot (DBS); Everolimus; LC-MS/MS; Sirolimus; Therapeutic drug monitoring (TDM).